Gamified Interaction Empowering Exhibition XR: A Review of Practical Cases and Research into Integration Pathways Gamified Interaction Enhances Exhibition XR: A Review of Practical Cases and Research on Integration Pathways - Yuan, Qican (Transactions on Environment, Energy and Earth Sciences, 2026)
At present, XR technology is driving a transformation in exhibitions. This shift is moving beyond ‘static displays’. It is moving toward ‘immersive experiences. However, the industry widely faces some challenges. The interactive features often lack variety. User engagement remains insufficient. The efficiency of cultural information dissemination can be improved. User retention rates also need enhancement. Exploring the value of integrating gamified interactions has now become essential. This approach is key to breaking through the current bottleneck. This paper focuses on the need to upgrade XR experiences in exhibitions. It examines this need within the context of digital media technology. This article systematically reviews typical XR applications from the exhibition and gaming fields. It integrates theories of virtual interaction design. The paper then provides an in-depth discussion on how gamified interactive elements can enhance the exhibition experience. Research indicates that current XR exhibitions have limitations. These exhibitions are primarily focused on viewing. Their interactive elements are often weak. Exhibitions can adopt gamified design methods. These methods include mission systems, operational feedback, and branching narratives. Such approaches significantly boost user engagement. This paper integrates practical cases like ‘The Vanishing Pharaoh’ and ‘Floating Dunhuang’. It also draws on game design principles from titles such as ‘Half-Life: Alyx’ and ‘Beat Saber’. Based on this, the study constructs a fusion framework of ‘Technical Adaptation, Content Anchoring, and Layered Design’. This framework offers theoretical guidance for gamified innovation in the XR exhibition field. It also provides a practical path for implementation.
Keywords: Gamified interaction; Exhibition XR; Virtual interaction design; Practical cases; Convergence pathways.